Peran Media dan BAWASLU dalam Menangani Penyebaran Hoaks dan Pemberitaan yang Akurat Pada Pemilihan Serentak 2024 Sesuai UU No. 40 Tahun 1999 Tentang Pers - Manurung, Maria Gontina; Siregar, Hisar (Universitas Pahlawan Tuanku Tambusai, 2025)
The political journey in Indonesia post-reform has often experienced fluctuations, with stagnation in political participation reflected in the decline in both the quality and quantity of voter participation, especially in general elections. Several regions still face high levels of abstention (golput), driven by dissatisfaction with the performance of political parties and figures, as well as the threat of negative practices such as vote-buying that influence voter decisions. To address these issues, efforts are needed to enhance public participation and enforce sanctions against money politics. The success of the elections also depends on the role of the media as a tool for monitoring and disseminating information that shapes public opinion, while educating the public about their rights and responsibilities as voters. This study aims to describe and analyze the role of the media in reporting on Bawaslu in accordance With Law No. 40 Of 1999 On The Press during the 2024 Simultaneous Elections, as well as the role of Bawaslu and the media in preventing the spread of hoaxes that undermine the integrity of the elections. Using a qualitative research method with a normative approach and Focus Group Discussions (FGD) with media and journalists, this study is expected to provide recommendations for improving the quality of news reporting and voter education to ensure democratic, fair, and transparent elections.